Detecting bubbles in the Brazilian commercial real estate market: 2012-2023 - Mira, Enrico Campos de (2024)
This research examines the dynamics of commercial real estate prices in the Brazilian market, exploring the potential presence of speculative movements within the real estate market for the period 2012-2023. The study utilizes a conventional present value asset pricing model with a consistent discount factor and employs established bubble tests from the finance literature. These tests encompass assessments for explosive bubbles, periodic bubbles, multiple explosive bubbles and intrinsic bubbles. As a result, this approach allows us to diagnose unsustainable trends in the trajectory of real estate asset prices, should speculative bubbles be detected within the series. Utilizing data from the Fipezap survey provided by the Institute of Economic Research Foundation (FIPE), the study identifies evidence of periods marked by price exuberance, as indicated by the explosive bubble test and the multiple bubble test for some cities and the national price index. However, using the corresponding tests, no evidence of periodically collapsing bubbles and intrinsic bubbles was found across any of the considered cities.